2010
DOI: 10.1590/s1984-70332010000400005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of maize core collection for drought tolerance

Abstract: -The maize genebank (GBmaize) preserves nearly 4,000 accessions for conservation and use. The use is however restricted because the accessions do not perform as well as the elite genotypes. This problem can be reduced by prebreeding, i.e., by extending the information on germplasm and introgressing useful alleles. Since irregular rainfall distribution and drought induce maize yield losses, drought tolerance is a main breeding target. In this study, the GBmaize accessions were evaluated for drought tolerance. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 14 publications
0
11
0
4
Order By: Relevance
“…The coefficients of variation (CVs, %) differed between LN and IN conditions only for NUEVT (Tables 1 and 2). Studies have shown that higher CVs are normal in nutrient-deficient conditions, because the trait means are generally lower under stress, and square means and standard deviations are higher (Soares et al, 2011). However, in general, the CV estimates were high.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The coefficients of variation (CVs, %) differed between LN and IN conditions only for NUEVT (Tables 1 and 2). Studies have shown that higher CVs are normal in nutrient-deficient conditions, because the trait means are generally lower under stress, and square means and standard deviations are higher (Soares et al, 2011). However, in general, the CV estimates were high.…”
Section: Resultsmentioning
confidence: 96%
“…For the other traits, there was no significant difference among inbred lines between the two N levels. Presterl et al (2003) and Soares et al (2011) found that NE, EW, and TY have their expression reduced when assessed under low N conditions. However, some studies showed that the application of contrasting N levels -even when the amounts differed greatly -had no effect on corn yield (Cruz et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As avaliações já conduzidas visando agregar valor ao BAG Milho consideraram, em sua maioria, o desempenho dos acessos per se (Miranda Filho et al, 2000;Andrade et al, 2002;Teixeira et al, 2002Teixeira et al, , 2010 …”
Section: Resultsunclassified
“…Dentre esses estudos, já foram enfocadas a adaptação às condições ambientais especificas, tal como as condições de estresse de seca (Teixeira et al, 2010) e aos estresses bióticos (Miranda Filho et al, 2000;Teixeira, et al, 2013). Miranda Filho et al (2000) avaliaram mais de 1.000 acessos do BAGMilho quanto à tolerância a cinco patógenos e também desenvolveram cinco compostos-fontes de resistência a patógenos.…”
unclassified